Study of China’s Publicity Translations Based on Complex Network Theory - Lisong Wang; Rui Song; Zhao Qu; Han Zhao; Chenmiao Zhai (IEEE Access, 2018)
Translation is a complex activity in which two language systems form complex network structures. This paper aims to examine the similarities and differences between English language and Chinese language publicity material networks and to reveal the core factors manifested in the publicity materials by choosing 1000 pieces of Chinese and English publicity materials as the study objects (500 pieces in each language). The core factors of 10 contemporary translation theories identified by the Delphi method are considered nodes; then, we link the nodes in accordance with their relevance among the core factors embodied in the translated publicity materials to draw network diagrams (the English language and Chinese language publicity material networks). Finally, we discuss appropriate contemporary translation theories that are suitable for guiding China's publicity translations and explore a new research perspective for the study of China's publicity translations.